A Study of Applicability of Hamilton Depression Rating Scale in A Tertiary Psychiatry Clinic of Kolkata - Malay Ghosal; Asish Debnath; Sukhendu Mondal; Ranadip Chowdhary; Sarmila Mallik (Medsci Publications, 2012)
Background: According to WHO, Depression has been ranked fourth in the list of most urgent health problem Worldwide. One of the thumbing blocks in assessing depression is the lack of objective set of measurements for its diagnosis. Most often used is still the Hamilton Depression Scale (HAM-D) besides Montgomery Asberg Depression Scale is increasingly used in antidepressant drug trials. Objective: The objective of the study is to single out the unnecessary items of HAM-D, to develop a shorter form of the scale excluding such items and then validate it against Montgomery-Asberg Depression Rating scale (MADRS)-an acceptable, standard scale for measuring depression in socio- demographic set up like that of India. Methods: After identifying the patients with inclusion and exclusion criteria; two separate clinician of Psychiatry department of Calcutta Medical College used HAM-D & MADRS,  one  used  HAM-D  & other MADRS in one time, and in other time it is reversed. Two are totally blind to each other, to whom they used what scale in each time. Then the data were analysed for reliability and validity of HAM-D in SPSS 16.0 version. Results: The internal consistency of HDRS-17 is Cronbach's Alfa is 0.674.. Scale-mean with item 9 deleted is 20.27 & if item 17 is deleted then scale mean is 20.15. The Cronbach's alpha is very similar if the item-9 & 17 are deleted. Conclusion: It can be concluded that as HDRS and MADRS have different levels of sensitivity over the severity spectrum of Depression, none of them is singularly satisfactory in assessment of Depression severity in the study population.